2014
DOI: 10.1021/ic500327s
|View full text |Cite
|
Sign up to set email alerts
|

Technetium and Rhenium Pentacarbonyl Complexes with C2 and C11 ω-Isocyanocarboxylic Acid Esters

Abstract: Technetium(I) and rhenium(I) pentacarbonyl complexes with ethyl 2-isocyanoacetate and methyl 11-isocyanoundecanoate, [M(CO)5(CNCH2COOEt)]ClO4 (M = Tc (1) and Re (2)) and [M(CO)5(CN(CH2)10COOMe)]ClO4 (M = Tc (3) and Re (4)), were prepared and characterized by IR, (1)H NMR, and (13)C{(1)H} NMR spectroscopy. The crystal structures of 1 and 2 were determined using single-crystal X-ray diffraction. The kinetics of thermal decarbonylation of technetium complexes 1 and 3 in ethylene glycol was studied by IR spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
(33 reference statements)
3
10
0
Order By: Relevance
“…Figure illustrates the 99 Tc NMR spectrum of 7 with a Tc–P coupling to the axial PPh 3 ligands of 549 Hz. Such couplings are in accord with those observed in the other few [Tc­(L)­(CO) 2 ­(PPh 3 ) 2 ] complexes, where L represents chelating dithioligands. …”
Section: Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Figure illustrates the 99 Tc NMR spectrum of 7 with a Tc–P coupling to the axial PPh 3 ligands of 549 Hz. Such couplings are in accord with those observed in the other few [Tc­(L)­(CO) 2 ­(PPh 3 ) 2 ] complexes, where L represents chelating dithioligands. …”
Section: Results and Discussionsupporting
confidence: 88%
“…Despite the fact that with the development of 99m Tc sestamibi an isonitrile complex of technetium­(I) became one of the most used radiopharmaceuticals worldwide, , the fundamental coordination chemistry of technetium with this class of ligands is relatively little explored. Most of the Tc isocyanide complexes contain the metal in low oxidation states. In a recent report, also the access to corresponding nitrido and phenylimido complexes of technetium­(V) is described . The stabilization of high oxidation states became possible by the use of sterically encumbered terphenylisocyanides, which allowed the tuning of bonding properties in a wide range.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The synthesis of pentacarbonyltechnetium(I) complexes with one additional isocyanide ligand can readily be performed by a selective exchange of a halide from [Tc(CO) 5 X] species (X = Cl, Br, I). Such reactions are commonly conducted under mild conditions and with the addition of Ag + ions as halide scavengers, 30,31 while heating of the pentacarbonyl halides with an excess of isocyanides results in the formation of neutral tricarbonyl compounds of the composition fac-[Tc(CO) 3 X-(CNR) 2 ]. 32,33 Such facial tricarbonyltechnetium(I) complexes are also obtained during reactions of (NEt 4 ) 2 [Tc(CO) 3 Cl 3 ] or (NBu 4 )[Tc 2 (CO) 6 (μ-Cl) 3 ] (Scheme 1) with alkyl isocyanides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To estimate the stability of these complexes in a simulated biological medium, we added excess histidine to an aqueous solution of [ 99 Tc(PTA)(CO)5]ClO4. The IR spectra showed that the complex is resistant to "histidine challenge" for at least 24 h. It should be noted that [ 99 Tc(NCR)(CO)5]ClO4 are less stable under these conditions [23]. The CAP complexes are also stable with respect to histidine challenge reaction (Fig.…”
Section: Behavior Of the Pentacarbonyl Phosphine Complexes In Aqueous Solutionsmentioning
confidence: 94%